Identification of Pests and Diseases on Coconut (Cocos nucifera L.) in Sangihe Island Regency, North Sulawesi Province, Indonesia - Alisya Talita Papona; Efi Toding Tondok; Bonjok Istiaji (Agriprima : Journal of Applied Agricultural Sciences, 2023)
As an archipelago regency, the Sangihe Islands has been known for its expanses of coconut plantations, which are one of the local community's primary commodities and sources of income. An inventory of pests and diseases specific to coconut in this area has never been carried out, and this information is needed, especially regarding sustainable coconut management. This study aimed to determine the presence of coconut pests and diseases in Sangihe and to obtain the latest conditions related to pests and disease incidence. The research was carried out through several stages, i.e., interviewing farmers, sampling, and identifying and documenting pests and diseases. The climate condition of Sangihe Island is classified as type A (very wet), with an average rainfall of 248 mm, temperature of 27 C, and humidity of 83% from 2017-2021. This condition is one of the determining factors for the existence of pest attacks and disease-causing pathogen infection on coconut. Pests dominated as disturbing organisms compared to diseases caused by plant pathogens. These pests included grasshoppers, coconut rhinoceros beetles, coconut hispine beetles, coconut mites, and white-tailed mice. Observations of the damage intensity by Sexava coriaceae were conducted in the Tahuna Barat district by selecting three land categories. The most severe damage occurred in field B (mostly planted with Hybrid Coconuts) with a percentage of 39%, while the lowest damage was in field C (mostly planted with Tall Coconuts), at 17%. The major disease detected was a gray leaf spot caused by the fungus Pestalotiopsis palmarum. The highest disease incidence and severity were found in Tabukan Utara district with percentages of 43% and 22% respectively, while the lowest incidence and severity were found in Tahuna Barat district with percentages of 3% and 1%, respectively.